Factors Influencing Students’ Enrolment and Retention in Sciences at Advanced Level in Secondary Schools in Uganda: A Case of Kabale Municipality Secondary Schools. - Akatuhurira, Frank Bindeba (Kabale University, 2023)
A correlational study was carried out on the factors influencing students' enrolment and retention in sciences at the advanced level in secondary schools in Kabale Municipality, Uganda. The study adopted both quantitative and qualitative approaches, with questionnaires and interview guides as the primary tools for data collection. The study focused on the physical learning environment, students' attitudes towards sciences, and the quality of science teachers, and how these factors influenced students' enrolment and retention in sciences at the ‘A’ level. The findings of the study indicated that the availability of enough apparatus in the laboratories, a cool temperature to encourage learning, and students' social status defined their attitudes towards sciences. Additionally, inadequate professional training affected science teaching. Based on the study's conclusions, the enrolment and retention of students in sciences at the advanced level of secondary schools in Kabale Municipality were influenced by a conducive physical learning environment, students' attitudes towards sciences, and the quality of science teachers. The study recommends addressing acoustic conditions in classrooms, encouraging a cool temperature for learning, providing government aid to secondary schools for infrastructure development, and employing professional science teachers.